Venus förvisning och återkomst: Om Skogekär Bergbos Wenerid som tillfällesskrift - Gustafsson, Lars (Tidskrift för litteraturvetenskap, 2012)
The Banishment and Return of Venus: Skogekär Bergbo’s Wenerid as Occasional Poetry This article deals with the Swedish sonnet sequence Wenerid, written by the pseudonym Skogekär Bergbo in the tradition of Petrarch. It was published in 1680 but, according to the author, written ”more than thirty years ago”, during the reign of Queen Christina. At her court, expectations that the young queen would soon marry found expression for instance in court ballets. Skogekär Bergbo was possibly the author of the Swedish texts of a couple of such ballets. Similarly, his Wenerid could be interpreted as part of the homage paid at court to the power of love. Queen Christina decided, however, not to marry, and literary tributes to Venus were no longer desirable at her court. This could perhaps explain why Wenerid was not published during her reign. 1680 was the year of the marriage between King Charles XI and the Danish princess Ulrika Eleonora. It seems plausible to relate the publication of Wenerid in 1680 to the wedding of the royal couple and the coronation of the new queen. But the book bears no dedication, and it cannot, as has been proposed, be regarded as occasional poetry for the royal festivities. It is, however, possible that the poet saw an opportunity of bringing to the fore an aristocratic culture which had flourished in the days of Queen Christina. One of the manifestations of this culture was courtly Petrarchism and the cult of the goddess of love. 1680, the year of the royal wedding, was a favourable time for the return of Venus, and of Wenerid.